Development of Electronic Student Worksheet Based on Cooperative Learning in IPAS Subject for Grade V Elementary School Students - Rahlia Ayu Putri; Alwen Bentri; Abna Hidayati; Ramalis Hakim (Jurnal Penelitian Pendidikan IPA, 2025)
Low student participation in IPAS learning, limited instructional media, and reliance on printed materials at SD Kartika I-10 Padang have negatively affected students’ understanding. This study aimed to develop an electronic student worksheet (E-LKPD) based on cooperative learning that meets the criteria of validity, practicality, and effectiveness for fifth-grade IPAS learning. The research applied a Research and Development (R&D) design using the ADDIE model, which includes Analyze, Design, Development, Implementation, and Evaluation. The subjects were 22 fifth-grade students. The development process involved analyzing needs, curriculum, and student characteristics, designing visual and content aspects of the E-LKPD, validating with media, material, and language experts, followed by product revision, implementation, and evaluation. Data were collected through expert validation sheets, teacher and student practicality questionnaires, and pretest-posttest. Results indicated high validity with an average score of 95%, while practicality was rated very practical by teachers (95%) and students (88%). Student learning outcomes improved significantly, with mean pretest and posttest scores of 56.59 and 90.45, respectively. The Wilcoxon test confirmed a significant difference (Z = -5.735, p < 0.05), reliability reached 0.80038 (reliable), and the N-Gain score was 0.79 (79.37%) in the high category. These findings conclude that the cooperative learning-based E-LKPD is valid, practical, and effective for enhancing IPAS learning in elementary schools.